Challenges and successes of research capacity building at a rural South African university - Singh, Rachael Jesika (South African Journal of Higher Education, 2016)
In the South African context, rural universities are labelled ‘historically disadvantaged’ and are faced with numerous challenges regarding research capacity development. It is against this background that this article examines the challenges faced at the University of Limpopo, in the area of research capacity building. A multi-pronged approach was adopted by the university to build research capacity. This approach involved increasing the number of accredited publications by staff, training supervisors, increasing the number of staff who has doctorates, providing support for female researchers, increasing awareness around funding opportunities, research support for postgraduate students and incentives for staff that publish and supervise postgraduate students. Data was obtained from research statistics compiled by the university, approved policy and incentive documents of the university, and evaluative and reflective feedback from participants in different support programmes. The data was both quantitatively and qualitatively analysed. The findings revealed that there is an increase in the capacity building initiatives of the university in the last four years. This is reflected in an increase in research output. The paper recommends that institutional research capacity building be approached from a context-specific perspective.